Accuracy of bite mark analysis from food substances: A comparative study - Daniel, M. Jonathan (J Forensic Dent Sci, 2015)
AIMS AND OBJECTIVES: The aims and objectives of the study were to compare the accuracy of bite mark analysis from three different food substances-apple, cheese and chocolate using two techniques-the manual docking procedure and computer assisted overlay generation technique and to compare the accuracy of the two techniques for bite mark analysis on food substances. MATERIALS AND METHODS: The individuals who participated in the study were made to bite on three food substances-apple, cheese, and chocolate. Dentate individuals were included in the study. Edentulous individuals and individuals having a missing anterior tooth were excluded from the study. The dental casts of the individual were applied to the positive cast of the bitten food substance to determine docking or matching. Then, computer generated overlays were compared with bite mark pattern on the foodstuff. RESULTS: The results were tabulated and the comparison of bite mark analysis on the three different food substances was analyzed by Kruskall-Wallis ANOVA test and the comparison of the two techniques was analyzed by Spearman's Rho correlation coefficient. CONCLUSION: On comparing the bite marks analysis from the three food substances-apple, cheese and chocolate, the accuracy was found to be greater for chocolate and cheese than apple.